PENGAWASAN DALAM UPAYA PENATAAN DAN PEDOMAN MENARA TELEKOMUNIKASI DI KOTA PEKANBARU - Rani Indriatun; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Planning and supervision in an effort Guidelines Telecommunication Tower in the city of Pekanbaru. This study aims to determine how supervision and guidance in the arrangement of a telecommunications tower in the City Pekanbaru.Penelitian which is descriptive qualitative data collection was done by using snowball. The results show the arrangement and supervision guidelines in Pekanbaru city is still not performing well.This is evidenced by the many telecommunications tower that is not in accordance with the standards that have been set in regulations on guidelines for structuring shared telecom towers in the city of Pekanbaru.Keywords : Supervision, Structuring of telecom tower, Pedoman Menara